2022
DOI: 10.1099/jgv.0.001810
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of viruses associated with the parasitoid Anagyrus vladimiri (Hymenoptera: Encyrtidae)

Abstract: Knowledge on symbiotic microorganisms of insects has increased dramatically in recent years, yet relatively little data are available regarding non-pathogenic viruses. Here we studied the virome of the parasitoid wasp Anagyrus vladimiri Triapitsyn (Hymenoptera: Encyrtidae), a biocontrol agent of mealybugs. By high-throughput sequencing of viral nucleic acids, we revealed three novel viruses, belonging to the families Reoviridae [provisionally termed AnvRV (Anagyrus vladimiri reovirus)], Iflaviridae (AnvIFV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Finally, Telenomus podisi (Platygastridae), an egg-parasitoid wasp found in Brazil and in the United States [23], has been shown to be important in controlling its preferential host Euchistus heros, an abundant pest of soybean crops [24,25]. Previous research focused on parasitoid wasps' virome revealed the presence of members of Reoviridae, Iflaviridae [26], Dicistroviridae [27,28], Lispiviridae, Rhabdoviridae [29], and Nyamiviridae [30]. However, exogenous RNA viruses of these insects are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Telenomus podisi (Platygastridae), an egg-parasitoid wasp found in Brazil and in the United States [23], has been shown to be important in controlling its preferential host Euchistus heros, an abundant pest of soybean crops [24,25]. Previous research focused on parasitoid wasps' virome revealed the presence of members of Reoviridae, Iflaviridae [26], Dicistroviridae [27,28], Lispiviridae, Rhabdoviridae [29], and Nyamiviridae [30]. However, exogenous RNA viruses of these insects are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%